De novo Vessel Formation Through Cross-Talk of Blood-Derived Cells and Mesenchymal Stromal Cells in the Absence of Pre-existing Vascular Structures - Rüger, Beate M.; Buchacher, Tanja; Dauber, Eva-Maria; Pasztorek, Markus; Uhrin, Pavel; Fischer, Michael B.; Breuss, Johannes M.; Leitner, Gerda C. (Frontiers in Bioengineering and Biotechnology, 2020)
The generation of functional blood vessels remains a key challenge for regenerative medicine. Optimized in vitro culture set-ups mimicking the in vivo perivascular niche environment during tissue repair may provide information about the biological function and contribution of progenitor cells to postnatal vasculogenesis, thereby enhancing their therapeutic potential. We established a fibrin-based xeno-free human 3D in vitro vascular niche model to study the interaction of mesenchymal stromal cells (MSC) with peripheral blood mononuclear cells (PBMC) including circulating progenitor cells in the absence of endothelial cells (EC), and to investigate the contribution of this cross-talk to neo-vessel formation. Bone marrow-derived MSC were co-cultured with whole PBMC, enriched monocytes (Mo), enriched T cells, and Mo together with T cells, respectively, obtained from leukocyte reduction chambers generated during the process of single-donor platelet apheresis. Cells were embedded in 3D fibrin matrices, using exclusively human-derived culture components without external growth factors. Cytokine secretion was analyzed in supernatants of 3D cultures by cytokine array, vascular endothelial growth factor (VEGF) secretion was quantified by ELISA. Cellular and structural re-arrangements were characterized by immunofluorescence and confocal laser-scanning microscopy of topographically intact 3D fibrin gels. 3D co-cultures of MSC with PBMC, and enriched Mo together with enriched T cells, respectively, generated, within two weeks, complex CD31+/CD34+ vascular structures, surrounded by basement membrane collagen type-IV+ cells and matrix, in association with increased VEGF secretion. PBMC contained CD31+CD34+CD14-CD45dim progenitor-type cells, and EC of neo-vessels were PBMC-derived. Vascular structures showed intraluminal CD45+ cells that underwent apoptosis thereby creating a lumen. Cross-talk of MSC with enriched Mo provided a pro-angiogenic paracrine environment. MSC co-cultured with enriched T cells formed ‘cell-in-cell’ structures generated through internalization of T cells by CD31+CD45dim/- cells. No vascular structures were detected in co-cultures of MSC with either Mo or T cells. Our xeno-free 3D in vitro vascular niche model demonstrates that a complex synergistic network of cellular, extracellular and paracrine cross-talk can contribute to de novo vascular development through self-organization via co-operation of immune cells with blood-derived progenitor cells and MSC, and thereby may open a new perspective for advanced vascular tissue engineering in regenerative medicine.